How to Enlarge the Scope of the Curriculum Integration of Mathematics and Science (CIMAS): A Delphi Study - Kim, Minkee; Aktan, Tugba (EURASIA Journal of Mathematics, Science & Technology Education, 2014)
Studies have not yet consented whether integrating mathematics into science would enhance students' learning or confuse their understanding of abstract mathematical concepts. In spite of the social need for solving social-scientific problems with multiple facets, there has not been a holistic integration model of the disciplines. Hence, this study aims to propose a theoretical model for curriculum integration of mathematics and science (CIMAS) and to examine experts' opinions about its educational perspectives. The model captures appropriate topics, needs (pedagogical, motivational, and societal), and constraints. In spite of the small size of participants–23 mathematics educators in Ankara, their diverse integration examples reached to the conclusion that all units in the Turkish mathematics curriculum can be integrated with physics, chemistry, or biology (e.g., derivative with linear velocity, ratio with chemical mixture, and probability with genetics), while identifying the most number of examples with physics topics. The expert responses consistently clarified that CIMAS would enhance mathematics education for the pedagogical, motivational, societal, and other needs. However, the integration was also perceived to associate with obstacles with teachers, curricula, and facilities for effective implementation. Lastly, this study further presents a key discussion on how to enlarge the scope of CIMAS in terms of collaboration among mathematics educators.